Mainstreamed genetic testing for women with ovarian cancer: first-year experience. Issue 3 (13th March 2018) - Rahman, Belinda; Lanceley, Anne; Kristeleit, Rebecca S; Ledermann, Jonathan A; Lockley, Michelle; McCormack, Mary; Mould, Tim; Side, Lucy
Abstract : Background: Ovarian cancer is the fifth most common cause of cancer death for women in the UK. Up to 18% of cases can be attributed to germline mutations in BRCA1 and BRCA2 genes. Identifying patients who carry a BRCA mutation provides important information about potential response to treatment and eligibility for therapies such as poly ADP ribose polymerase (PARP) inhibitors. Implementation of systematic genetic testing of patients with ovarian cancer via oncology clinics (mainstreamed genetic testing, MGT) is increasing. Methods and results: This service evaluation reports on the first year of MGT at a tertiary oncology centre in London, UK. In total, 122 patients with high-grade non-mucinous ovarian cancer underwent BRCA germline testing via MGT. Eighteen patients (14.8%) were found to carry a deleterious BRCA1 / BRCA2 mutation. Four BRCA carriers did not meet previous criteria for genetic testing and would have been missed. Six BRCA carriers accessed PARP inhibitors post-MGT. Only 22% of patients with a variant of unknown significance (VUS) were referred to clinical genetics services. Conclusions: MGT appears to be a feasible way of providing BRCA testing to patients with ovarian cancer. Greater clarity of how oncologists use VUS results is needed, as well as further research on psychosocial implications of MGT for patients with ovarian cancer, which may include somatic testing in the future.